THE CHANGING ROLE OF HEALTH PROFESSIONALS DURING COVID-19: PERSPECTIVES ON NURSING - Masheal Masoud Alyami, Ghayeb Sayyah Alazmy, Mashael Salem Almuzail, Mubarak Muter Albnagi, ⁠deem Rahil Alfhimani, Meteb Ibrahim Alanazi, ⁠tahani Saad Alghamdi, Rahma Khader Almadani, Monifa Mayof Saud Alanazi, Jawaher Mayof Saud Alanazi, ,; Meznah Gabar Humaid Almalky, Amani Salah Fahad Alamri, Najlaa Manawer Gasham Alshmmari, Abdullah Saeed M Almalki, Khadijah Harown Hawsawi, Magda Saad Khamis Althalabi, (Chelonian Research Foundation, 2022)
The virus known as COVID-19 is a novel coronavirus that was identified in Wuhan, China in 2019. Nurses and other healthcare professionals (HCPs) are referred to as front-line health workers (FHWs) since they are essential members of the team that is attempting to save many lives. Leading health organizations and academic journals have consistently discussed the difficult role that HCPs must play in relation to multidisciplinary approaches and support systems, as well as the implications of evidence-based research for providing the highest caliber of care. However, this review produced four main categories: challenges, domains, support systems (such as codes of ethics), and evidence-based synthesis of health policy. Going a step further, this essay will address the important concerns of the nurses' thoughts on the impact of COVID-19 as well as the amazing role of courageous healthcare professionals, such as nurses and pharmacists, who demonstrated themselves to be health warriors. Keywords: evidence-based synthesis, domains, difficulties, therapeutic interaction, and multidisciplinary team.